(untitled) (Balneo and PRM Research Journal, 2024)
Background: Explosive strength or muscle power plays a decisive role in the motor performance of all athletes. Purpose: Analysis of muscle strength variations for female students of the Faculty of Physical Education and Sport/undergraduate level, according to sports specializations. Material and method: The study included 77 women (age = 20.48 ± 1.37 years, weight = 58.79 ± 8.92 kg, height = 166.24 ± 7.13 cm), divided into 3 evaluation subgroups (Non-athletes/NA = 40 cases, Team sports games/TSG = 17 cases and IS/Individual sports = 20 cases). Explosive strength rating was based on 7 lower body tests and 6 upper body tests. Manova parametric techniques were applied. Results: The analysis of variance indicates significant differences between the 3 defined groups, the F values correspond to thresholds p <0.05. Pairwise analysis highlights the statistical superiority of TSG and IS groups compared to NA. We noted better values of the TSG group of women in all upper body strength assessment tests, but these differences are not significant (p>0.05). Top performance values are dominated by sprinters and volleyball players for the lower body, respectively by handball, volleyball and karate players for the upper body, as-pects confirmed by the studied sources. Conclusion: We did not identify significant differences between the groups of athletes (TSG and IS), and the top values according to sports specialization reinforce the results of other similar studies, the specific effort obviously infusing the performance in the muscle strength tests.